Comparative Study on Quorum Modulatory Effect of Selected Medicinal Plants on Chromobacterium violaceum ATCC 12472 (MTCC 2656) - Nadasha Koonath Vijayan; Habibu Tanimu; Bindhu Omana Sukumaran (Journal of Pure and Applied Microbiology, 2024)
Among the main global health concern is the rampant rise in antibiotic resistant bacteria. One of the appealing and promising strategies to combat this menace is to target the adaptive mechanism called quorum sensing (QS) used by bacteria to survive. Exploratory research on anti-QS compounds derived from natural products has been a promising area. The present study investigated methanolic extracts from 26 plants to compare their anti-QS activity using the QS biosensor strain Chromobacterium violaceum American Type Culture Collection (ATCC 12472) (Microbial Type Culture Collection MTCC2656). QS-mediated violacein pigment inhibition was carried out using agar well diffusion method with concentrations ranging from 10 mg/ml to 100 mg/ml. Leaf extracts of Mangifera indica and Pimenta dioica and peel extract of Punica granatum were the only three plants found to exhibit violacein inhibitory potential till 10 mg/ml. The result of the minimum inhibitory concentration (MIC) showed 1.6 mg/ml for M. indica and P. dioica and 6.25 mg/ml for P. granatum. Further, violacein inhibitory properties of these extracts at and below MIC were evaluated by well diffusion assay (qualitative) and by flask incubation assay (quantitative). The zone of inhibition (well diffusion assay) was found to be 14.51 ± 0.63 mm to 10.37 ± 0.68mm for M. indica, 15.23 ± 0.57 mm to 9.62 ± 1.29 mm for P. granatum and 17.01 ± 0.1 mm to 13.14 ± 0.18 mm for P. dioica. The inhibitory effect of the plant extracts via quantitative assay on violacein ranged from 83-49%, 89-81%, and 89-49% for M. indica, P. granatum, and P. dioica respectively. Our findings suggested the potential of M. indica, P. granatum, and P. dioica methanolic extracts as a source of effective inhibitors of QS-mediated violacein production.